Prolonged droughts, short‐term responses, and diaspora: the power of water and pilgrimage at the sacred cenotes of Cara Blanca, Belize. (20th April 2016) - Lucero, Lisa J.; Harrison, Jessica; Larmon, Jean; Nissen, Zachary; Benson, Erin
Abstract : Every society considers some aspect of water holy or sacred, which was the case for the ancient Maya, where everything in life was rainfall dependent. Pilgrimage to such places, where people interact and engage with the sacred to keep the world on course, was vital. When pilgrimage does not work, more drastic measures can result, as we attempt to show with the Classic Maya (250–900 CE). Several prolonged droughts between 800 and 900 CE, ultimately resulted in an urban diaspora from interior southern lowland centers (and their intricate reservoirs) and most hinterland areas. During droughts, the Maya intensified their visits and rites at sacred water places, such as cenotes (steep‐sided sinkholes filled by groundwater), to appease gods and ancestors. Excavation results from two structures near one cenote at Cara Blanca, Belize demonstrate via structure layout, artifact assemblages, and botanical remains, that the pool served as a pilgrimage destination for Maya who traveled from near and far to supplicate the gods to end the droughts—but it was to no avail. The Maya ultimately left this region that has some of the richest tropical soils in the world, and which in previous centuries had witnessed the emergence of the most powerful kings. People emigrated in all directions in search of water, land, and new opportunities. In the end, short‐term responses did not work, but drastic ones such as urban diaspora did. WIREs Water 2017, 4:e1148. doi. 10.1002/wat2.1148 This article is categorized under: Science of Water > Water and Environmental Change Human Water > Water as Imagined and Represented